Examining Post-Civil War Bilateral Relations Between India and Sri Lanka from the Perspective of Security Concern: The Triangular Connection: India, Sri Lanka, and the United States (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India is a near neighbour to Sri Lanka's west. Ideas, culture, religion, and even language havebeen traded back and forth between the two countries over their more than 2,500-year history together.The presidents of the two nations have met often in recent years, trade and investment have expanded,cooperation in the areas of development, education, culture, and defence have all increased, and bothcountries share a similar perspective on the most serious issues facing the globe. Over the last year, thetwo nations have strengthened their level of bilateral interaction on a number of fronts, making greatstrides in the execution of developmental aid programmes for the Internally Displaced Persons (IDPs)and other underprivileged sectors of the Sri Lankan population.The study's overarching goal is to provide light on the complex nature of the triangle connectionbetween India, Sri Lanka, and the United States as a result of the latter's foreign policies and the latter'sinternal politics, which have been dominated by the island nation's decades-long civil conflict.